2011
DOI: 10.1039/c1an15060j
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectromicroscopy of biochemistry in functional single cells

Abstract: Over the years Fourier-Transform Infrared (FTIR) spectroscopy has been widely employed in the structural and functional characterization of biomolecules. The introduction of infrared (IR) microscopes and of synchrotron light sources has created expectations that FTIR could become a generally viable technique to study both structure and reactivity in vivo, inside single cells, by performing measurements that up to a few years ago were the preserve of in vitro experiments on purified macromolecules. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 75 publications
0
70
0
Order By: Relevance
“…The cell-coated window was transferred to a custom-built solution sample holder for FTIR microscopy, as previously described. 38 All cell culture materials were purchased from Invitrogen (Invitrogen, Life Technologies, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell-coated window was transferred to a custom-built solution sample holder for FTIR microscopy, as previously described. 38 All cell culture materials were purchased from Invitrogen (Invitrogen, Life Technologies, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of cellular composition is reflected in the complexity of the resulting IR spectra. 38,39 However, the carbonyl stretching vibrations appear in a spectral region, between 1800 cm -1 and 2100 cm -1 , which is clear of other absorptions from the most abundant cellular components. We used a two-dimensional correlation spectroscopic (2D-COS) analysis to simplify the picture by identifying sets of bands attributable to specific chromophores.…”
Section: Fibroblast Uptake and Localization Of B 12 -Mncorm-1 And B 12mentioning
confidence: 99%
“…In this embodiment, the IR absorption spectrum of an individual cell is captured to directly identify the structure and function of intracellular macromolecules (Quaroni and Zlateva, 2011; Kazarian and Chan, 2013). The challenge in this strategy is primarily the signal saturation due to the strong IR absorption of water, which can be addressed by employing dehydrated samples (Romeo et al, 2004).…”
Section: Probing Single Cellsmentioning
confidence: 99%
“…Following the approach previously applied by several research groups [3,51,54] Liepic et al compared the IR spectra of prostate cancer cells DU-145, derived from brain metastasis and treated with ionizing radiation, collected using a synchrotron radiation and a single point detector, with spectra collected using a conventional global source and a focal play array (FPA) detector. Due to the small cell sizes, the S/N ratio was lower when using the global source and FPA detector.…”
Section: Ftir Microspectroscopymentioning
confidence: 99%
“…D 2 O is also widely used together with deuterated drugs, for studying drugs toxicity in human metabolism. An interesting study showed that D 2 O is more toxic to malignant animal cells than healthy ones [54]. ATR-FTIR spectroscopy was applied to study different cellular topics [5,13,18,20,35].…”
Section: Atr-ftir Spectroscopymentioning
confidence: 99%